Flexor tendon pulley injuries in climbing: causes, diagnosis and treatment - Pach, Magdalena; Nowak, Agnieszka; Michalczewska, Aneta; Fugas, Agnieszka; Wierzejska, Natalia; Chmielowiec, Zuzanna; Partyka, Alicja; Dziedzic, Mariola; Smykiewicz, Karolina; Dobrzańska, Justyna (Journal of Education, Health and Sport, 2024)
Finger flexor pulley injuries are the most common overuse injuries sustained by climbers. These injuries are caused by forceful gripping techniques specific to climbing, making them uncommon in non-climbing activities. With the growing popularity of climbing, there is a rising need for accurate diagnosis and improved treatment methods. This paper explores current diagnostic techniques, including physical examination, ultrasound, and magnetic resonance imaging. It also discusses treatment options, which range from conservative rehabilitation to surgery, depending on the severity of the injury. Finally, it emphasizes the importance of injury prevention through proper warm-up and avoiding excessive strain.